Cost-Effectiveness of Improving Health Care to People with HIV in Nicaragua - Edward Broughton; Danilo Nunez; Indira Moreno (Nursing Research and Practice)
Background. A 2010 evaluation found generally poor outcomes among HIV patients on antiretroviral therapy in Nicaragua. We evaluated an intervention to improve HIV nursing services in hospital outpatient departments to improve patient treatment and retention in care. The intervention included improving patient tracking, extending clinic hours, caring for children of HIV+ mothers, ensuring medication availability, promoting self-help groups and family involvement, and coordinating multidisciplinary care. Methods. This pre/postintervention study examined opportunistic infections and clinical status of HIV patients before and after implementation of changes to the system of nursing care. Hospital expenditure data were collected by auditors and hospital teams tracked intervention expenses. Decision tree analysis determined incremental cost-effectiveness from the implementers’ perspective. Results. Opportunistic infections decreased by 24% (95% CI: 14%–34%) and 11.3% of patients improved in CDC clinical stage. Average per-patient costs decreased by $133/patient/year (95% CI: $29–$249). The intervention, compared to business-as-usual strategy, saved money while improving outcomes. Conclusions. Improved efficiency of services can allow more ART-eligible patients to receive therapy. We recommended the intervention be implemented in all HIV service facilities in Nicaragua.